COMPARATIVE EVALUATION OF CLINICAL AND FUNCTIONAL CARDIAC PARAMETERS IN PATIENTS WITH HIBERNATING AND NON-HIBERNATING MYOCARDIUM - Kodirova Sh.K.; Kenzhaev M.L. (Central Asian Journal of Medicine, 2025)
The aim of this study was to compare the clinical and functional cardiac parameters before and after dobutamine administration in three categories of patients: those with anatomically and functionally healthy myocardium, with hibernating myocardium, and with non-viable (non-hibernating) myocardium. The results of echocardiographic assessment and hemodynamic changes allowed for evaluating the diagnostic value of the dobutamine stress test in the stratification of patients with ischemic myocardial dysfunction.